Leaf structure and histochemistry of the hardy evergreen Euphorbia characias L. (Mediterranean spurge) - Christodoulakis, N.S.; Mamoucha, S.; Termentzi, A.; Fokialakis, N. (Flora: Morphology, Distribution, Functional Ecology of Plants, 2015)
The dorsiventral, hypostomatic leaf of Euphorbia characias is investigated to disclose its structural features and the chemical nature of the secondary metabolites produced. Light and scanning electron microscopy along with histochemical tests were employed to investigate the leaf of this well known perennial dwarf Mediterranean shrub. The compact leaf is characterized by numerous, rather uniform, curly, unicellular hairs on both surfaces, vaulty protrusions of the outer periclinal walls of the epidermal cells, prominent on the lower epidermis in particular, and a network of latex producing ducts (laticifers) extending in two layers within the mesophyll. Histochemical reactions proved positive only for alkaloids within the laticifers and phenolic compounds, especially for the condensed tannins accumulated within the vacuole of the epidermal cells. GC-MS and GC-FID analyses of the latex revealed the presence of several secondary metabolites, mainly belonging to the class of triterpenes. Lanosterol, butyrospermol, cycloartenol and lupeol were the major constituents in the extract examined. © 2014 Elsevier GmbH.
Keywords: chemotaxonomy; Condensed tannins; Euphorbia; Euphorbia characias; evergreen tree; Histochemistry; histology; Laticifers; leaf; Leaf anatomy; Mediterranean environment; metabolite; Secondary metabolites; shrub; Triterpenes